Glycidol esters from diethylamido-(4-phenylthiazolyl-2-amido)-ketophosphonates and their chemical modification - Sal’keeva, L. K.; Minayeva, E. V.; Nurmaganbetova, M. T.; Kokzhalova, B. Z.; Mantel, A. I. (SP MAIK Nauka/Interperiodica, 2009)
Thiazolyl-containing esters of α-ketophosphonic acids (KPE) unknown earlier were synthesized and investigated in Darzens-Claisen reaction. Reactions were demonstrated to proceed by a classic scheme to form the corresponding phosphorylated glycidol esters whose alkaline hydrolysis gave rise to phosphorylated aldehydes of interesting nature.